2001
DOI: 10.1046/j.1460-9592.2001.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Transoesophageal echocardiographic monitoring during paediatric cardiac surgery: obtainable information and feasibility in 532 children

Abstract: These data stress the safety and ease of performing TOE in children undergoing cardiac surgery. There is evidence for benefit from TOE findings to potentially enhance the therapeutic basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Most would agree that the individual performing intraoperative TEE should meet established experience and training guidelines for pediatric TEE [30,73,74]. Although most examinations are performed by cardiologists, a number of pediatric cardiac anesthesiologists have been important contributors, advocates and performers of intraoperative pediatric TEE [75][76][77][78]. Sloth et al reported a series of 532 children in whom intraoperative TEE examinations were performed by anesthesiologists [75].…”
Section: Who Should Perform Intraoperative Tee?mentioning
confidence: 99%
See 2 more Smart Citations
“…Most would agree that the individual performing intraoperative TEE should meet established experience and training guidelines for pediatric TEE [30,73,74]. Although most examinations are performed by cardiologists, a number of pediatric cardiac anesthesiologists have been important contributors, advocates and performers of intraoperative pediatric TEE [75][76][77][78]. Sloth et al reported a series of 532 children in whom intraoperative TEE examinations were performed by anesthesiologists [75].…”
Section: Who Should Perform Intraoperative Tee?mentioning
confidence: 99%
“…Although most examinations are performed by cardiologists, a number of pediatric cardiac anesthesiologists have been important contributors, advocates and performers of intraoperative pediatric TEE [75][76][77][78]. Sloth et al reported a series of 532 children in whom intraoperative TEE examinations were performed by anesthesiologists [75]. There was but a single complication, one extubation.…”
Section: Who Should Perform Intraoperative Tee?mentioning
confidence: 99%
See 1 more Smart Citation
“…Transoesophageal echocardiography (TOE) has become a reliable intraoperative technique for assessing cardiac structure and function in infants and children with congenital heart disease undergoing cardiac surgery (1–3). Despite the widespread use of TOE.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown the impact of TEE on patients undergoing surgery for congenital heart disease. [4][5][6][7][8][9][10][11][12][13] Gallivan, et al [14] classified patients into three categories depending on surgical risk as an indication for performing intra-operative TEE: 1) Low risk; e.g., atrial septal defect (ASD), ventricular septal defect (VSD), valve replacement, and extracardiac procedures. 2) Moderate risk; e.g., atrioventricular (AV) I n t r a -o p e r a t i v e t r a n s -e s o p h a g e a l echocardiography (TEE) is an important monitoring and diagnostic tool used during surgery for repair of congenital heart disease.…”
mentioning
confidence: 99%